Mice with pituitary tumor transforming gene (pttg) knockout demonstrate increased urinary space in renal corpuscles - Varyvoda, O.Yu.; Yashchenko, A.M.; Lutsyk, A.D.; Bilyy, R.O.; Afanasiev, S.V.; Filyak, Ye.Z.; Stoika, R.S. (Вiopolymers and Cell, 2014)
Aim. To investigate the effect of knockout of the pituitary tumor transforming gene (pttg-1) on the morphometric parameters and carbohydrate determinants of the murine renal structures. Methods. Kidneys of the knockout mice in comparison with the wild type mice of BL6/C57 strain of 1 month and 1 year age were subjected to morphometric investigation and lectin histochemistry. Morphometric study was completed using ImagePro Plus and ImageJ software. Glycoconjugates were detected by means of 8 lectins possessing different carbohydrate affinities. Results. Knockout of the pttg-1 gene was accompanied by an increased (approx. 30 %) urinary space within the renal corpuscles, enhanced exposure of the LCA and PNA receptor sites, and reduced binding of the LABA, WGA and SNA lectins. Conclusions. This study suggests the effect of the pttg-1 gene products on processing and exposure of the carbohydrates in renal tissues, apparently affecting ultrafiltration of the primary urine.